A Narrative Review of Elementary Students' Difficulties in Identifying Main Ideas and Supporting Ideas in Indonesian Reading Instruction - Sindra Kirani; Rahayu Condro Murti; Fery Muhamad Firdaus; Cepi Safruddin Abdul Jabar (Journal of Innovation and Research in Primary Education, 2026)
The ability to identify main ideas and supporting ideas in paragraphs is a foundational reading comprehension competency in elementary education; however, Indonesian students consistently demonstrate low mastery of this skill, as reflected in national and international literacy assessments. This study employed a narrative literature review design, systematically searching the Google Scholar database and screening a final corpus of 22 peer-reviewed studies published between 2020 and 2025. Data were analyzed through a three-stage qualitative process comprising extraction, comparative analysis, and interpretive synthesis. The review identified three principal themes: (1) difficulties were pervasive across Grades 4–6, with 64.3% of studies documenting a persistent positional misconception about paragraph structure; (2) contributing factors were classified as internal (limited conceptual mastery, low reading motivation, metacognitive deficits) and external (low teacher instructional creativity, absence of engaging media); and (3) supporting idea difficulties were explicitly addressed in only 22.7% of reviewed studies, revealing a significant research asymmetry. These findings indicate that paragraph comprehension must be reconceptualized as a dual and interdependent competency. Problem-Based Learning, mind mapping, and multimodal media demonstrated consistent effectiveness in improving outcomes. This study contributes a holistic literacy framework that integrates main idea and supporting idea instruction, addressing a gap that prior reviews have not adequately theorized.